Abnormal angiogenesis in blood outgrowth endothelial cells derived from von Willebrand disease patients - Selvam, Soundarya N. (Blood Coagul Fibrinolysis, 2017)
Bleeding associated with angiodysplasia is a common, often intractable complication in patients with von Willebrand disease (VWD). Von Willebrand factor (VWF), the protein deficient or defective in VWD, is a negative regulator of angiogenesis, which may explain the pathologic blood vessel growth in VWD. OBJECTIVE: This study explores the normal range of angiogenesis in blood outgrowth endothelial cells (BOECs) derived from healthy donors and compares this to angiogenesis in BOECs from VWD patients of all types and subtypes. METHODS: BOECs were assessed for VWF and angiopoietin-2 (Ang-2) gene expression, secretion, and storage. To explore angiogenic potential we characterized cellular proliferation, matrix protein adhesion, migration, and tubule formation. RESULTS: We found great angiogenic variability in VWD BOECs with respect to each of the angiogenesis parameters. However, type 1 and 3 VWD BOECs had higher Ang-2 secretion associated with impaired endothelial cell migration velocity and enhanced directionality. Type 2A and 2B BOECs were the most proliferative and multiple VWD BOECs had impaired tubule formation in Matrigel. CONCLUSION: This study highlights the angiogenic variability in BOECs derived from VWD patients. Abnormal cell proliferation, migration, and increased Ang-2 secretion are common features of VWD BOECs. Despite the many abnormalities of VWD BOECs, significant heterogeneity amongst individual VWD phenotypes precludes a simple description of relationship between VWD type and in vitro surrogates for angiodysplasia.